Evaluasi pemakaian kelambu berinsektisida permethrin dalam pemberantasan malaria di propinsi lampung - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
A study of permethrine impregnated bed nets against the malaria vector Anophelessundaicusare reported and discussed. Field trial were carried out in Tarahan South Lampung. Houses were provided with 2 kinds of bed net made of cotton and nyllon impregnated with permethrine 25 EC at dosage of 0.50 g.a.i/m2. Entomological data which came from human-vector contact and resting were collected during the trial (1986-1988). The results showed that vector densities were decrease for about 2-4 months. The bioassay test revealed that 75.5 and 56.0% mortalities were obtained from impregnated cotton bed net and nyllon bed net respectively after using for about 6 months.